2021
DOI: 10.1007/s10113-021-01848-1
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ action space to adopt sustainable practices: a study of arable farming in Saxony

Abstract: The urgency to address climate change, biodiversity loss, and natural resource degradation requires major changes in agricultural practices. Agricultural policy in Germany has so far failed to generate such changes; meanwhile, public demands for new regulations are met by widespread farmers’ protests. Against this background, an improved understanding of the factors influencing farmers’ uptake of sustainable agricultural practices is necessary. This study introduces the concept of action space to analyze the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 86 publications
1
12
0
Order By: Relevance
“…To a large extent the findings presented here match and complement the findings from previous literature on behavioural barriers and enablers of environmentally friendly farming. For instance, Gütschow et al (2021) highlight the importance of increasing policy coherence, providing additional financial incentives (including, possibly, investment support) and reducing the bureaucratic burden in efforts to increase the uptake of agrienvironmental practices. The TDF analysis suggests that, in addition, training activities and a better demonstration of the benefits of agri-environmental practices could increase their uptake.…”
Section: Discussionmentioning
confidence: 99%
“…To a large extent the findings presented here match and complement the findings from previous literature on behavioural barriers and enablers of environmentally friendly farming. For instance, Gütschow et al (2021) highlight the importance of increasing policy coherence, providing additional financial incentives (including, possibly, investment support) and reducing the bureaucratic burden in efforts to increase the uptake of agrienvironmental practices. The TDF analysis suggests that, in addition, training activities and a better demonstration of the benefits of agri-environmental practices could increase their uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, this practice results in lower total costs of crop production (Mohring, Finger and Dalhaus, 2022). Gutschow, Bartkowski and Felipe-Lucia (2021) found that implementing diversified crop rotations as a CC mitigation strategy could be more economically viable. According to a survey among German farmers, most environmental-friendly practices are not perceived as a 'business-viable' strategy as they limit revenue margins and threaten the agribusiness's survival level (Gutschow, Bartkowski and Felipe-Lucia, 2021).…”
Section: Farmers In Developed Countriesmentioning
confidence: 99%
“…-Farmers are also aware to improve the environment (Maharjan, Gonzalvo and Aala, 2022a;Mohring, Finger and Dalhaus, 2022). -Although economic profits were found to be essential (Gutschow, Bartkowski and Felipe-Lucia, 2021;Schukat and Heise, 2021), knowledge, environmental resistance, and legislative issues were barriers for farmers in implementing sustainable agriculture practices (de Lauwere, Slegers and Meeusen, 2022). -An article has mentioned circular agriculture (de Lauwere, Slegers and Meeusen, 2022).…”
Section: Farmers In Developed Countriesmentioning
confidence: 99%
“…Farmers are often constrained by economic and legal factors, which in extreme cases may lead to path dependencies preventing the adoption of erosion-reducing practices. Involving them in transdisciplinary research efforts would allow taking their 'action space' to adopt such practices better into account (Gütschow et al, 2021). This would help design policies that maximize available synergy and co-benefit potentials between climate change adaptation, wind erosion control and the multiple private and public benefits provided by agricultural landscapes (e.g.…”
Section: Wind Eros I On a S A So Cial-environmental Phenomenonmentioning
confidence: 99%